Attitude towards Physical Activity; A Comparative study of Physical Educationists and Doctors - Muhammad Iqbal; Muhammad Imran Khan:; Muhammad Asmat Ullah Khan; Arslan Naveed; Muhammad Arslan Javed; Sadaf Manzoor; Junaid Khan (Al-Qanṭara, 2023)
This study examined 134 (61 male teachers; 44 female teachers; 17 male doctors; 22 female doctors) attitude towards physical activities from two Tehsils of Dera Ghazi Khan Division, Pujnab, Pakistan. The study at hand was conducted using modified version of the Attitude towards Physical Activities (ATPA) by Khan et al., (2012) while differences in the participants ATPA in respect of their gender and age were also examined. The main part of ATPA scale consisted of five different domains having 32 items with 5-points Likert Scale. Data analysis techniques included frequency, percentage, mean, Std. Deviation, t-test and ANOVA. Results indicated that participants’ attitude towards physical activity (ATPA) was positive (3.42 > 3.00). Profession, gender and age are three important factors that form and impacts on their ATPA differently whereas teachers reported higher mean score on overall attitude towards physical activity as compared with doctors (p=.001 < 0.05) and male teachers reported higher mean score on overall attitude towards physical activity as compared with male doctors (p=.003 < 0.05). Furthermore, female teachers reported higher mean score on overall attitude towards physical activity as compared with female doctors (p=.001 < 0.05). When comparing the group mean differences based on the age, the data indicated statistically significant difference in the mean score of overall attitude towards physical activity between the different age groups of the participants (p=.001 < 0.05). It has been concluded that attitude has paramount significance in shaping behaviour towards participation in physical activities. Hence, proper guidance may be given to students and general masses to develop attitude towards physical activities.